A scoping review on the body awareness rehabilitation after stroke: are we aware of what we are unaware? - Cardile, Davide; Lo Buono, Viviana; Corallo, Francesco; Quartarone, Angelo; Calabrò, Rocco Salvatore (Frontiers in Neurology, 2025)
Body awareness (BA) is a complex multi-dimensional construct that refers to the subject’s ability to consciously perceive and integrate sensory and proprioceptive information related to the position, movement, and balance of one’s own body and body parts. Since it involves multiple brain regions and include different functional networks, it is very often affected by cerebrovascular damage such as stroke. Deficits in the ability to monitor our actions and predict their consequences or recognize our body parts and distinguish them from those of others may emerge after stroke. In this study, we decided to explore whether specific treatments targeting BA are discussed in current literature, and whether BA is considered as an outcome in neurorehabilitation processes for stroke patients. To achieve our goal, a scoping review on this often-underreported problem was performed. After analyzing the existing literature, emerged BA in stroke patients is rarely assessed or rehabilitated through specific stimulation or rehabilitation protocol. Additionally, treatment outcomes related to BA are often considered only from a “physical” perspective such as improvements in walking, balance, or the movement of specific body parts, rather than from a proprioceptive standpoint. Further research is needed to facilitate developing early and effective intervention strategies for the recovery of BA after stroke.